2020
DOI: 10.3390/metabo10040163
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Lipidomics of Cardiovascular Disease Highlights the Importance of Isolating Lipoproteins

Abstract: Cutting-edge lipidomic profiling measures hundreds or even thousands of lipids in plasma and is increasingly used to investigate mechanisms of cardiovascular disease (CVD). In this review, we introduce lipidomic techniques, describe distributions of lipids across lipoproteins, and summarize findings on the association of lipids with CVD based on lipidomics. The main findings of 16 cohort studies were that, independent of total and high-density lipoprotein cholesterol (HDL-c), ceramides (d18:1/16:0, d18:1/18:0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 68 publications
2
77
0
Order By: Relevance
“…In humans, PCs with a higher degree of unsaturation (higher number of double bounds) appear to protect from diabetes progression, whereas an increased risk is associated with higher contents of saturated fatty acid chains [ 19 , 20 ]. Similar conclusions were reached by Ding and Rexrode [ 21 ] regarding the risk for cardiovascular diseases. Interestingly, such polyunsaturated PCs (PC ae C38:5, PC aa C40:6; Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In humans, PCs with a higher degree of unsaturation (higher number of double bounds) appear to protect from diabetes progression, whereas an increased risk is associated with higher contents of saturated fatty acid chains [ 19 , 20 ]. Similar conclusions were reached by Ding and Rexrode [ 21 ] regarding the risk for cardiovascular diseases. Interestingly, such polyunsaturated PCs (PC ae C38:5, PC aa C40:6; Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the correlation between lipids, FFA, and clinical parameters, a previous study reported that LPC are predominantly found in HDL, CER in LDL, and PC are present in both lipoproteins (HDL and LDL) 15 . Thus, FFA composition may also be important for the lipoprotein function and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, FFA composition may also be important for the lipoprotein function and metabolism. Studies examining CVD with lipidomics found that after adjusting for HDL-C and LDL-C levels, only PC remained associated with cardiovascular events 15,30,31,32,33,34,35 . Kolovou et al observed a correlation of SM, PC, PE, phosphatidylinositol, CEs and Tg in subjects with obesity, and a positive correlation between SM and LDL-C, and between LPC and VLDL-C, among subjects with familial hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of SM in reconstituted HDL is necessary to regulate ICAM-1 and to induce eNOS phosphorylation [ 11 ]. Therefore, the impact of SM seems to be related to the carrying lipoprotein [ 25 ]. In this study, the decrease of non-HDL-SM with no changes of HDL-SM may reflect an additional potential benefit of pomegranate as nutraceutical product.…”
Section: Discussionmentioning
confidence: 99%